Preparation of Sous Vide Chicken Rice and Chicken Keel - Tan, Cheng Huat (2005)
Time-temperature profiles and process time for sous vide chicken rice and chicken keels were obtained through heat penetration test. For 5 D processed chicken rice,the process time obtained by using General Method at 65,70,75,80 and 85ºC were 58.8min,34min, 23.5min, 18min and 14min. For 13 D processed chicken rice, the process time were 125.8 min, 61.8 min, 34.5 min, 24 min and 18.5 min, respectively. In slow heating(75oC) of chicken keel, the process time for 5 D and 13 D processes were 26.7 and 38.3 min whereas for the fast heating (90oC), were 16.5 and 19.2 min,respectively. Ball’s method could also be used for the computation of process time due to minor percentage of deviation from General Method (4 - 14% for all the process time computed above).Traditional cooked chicken rice (the reference) with pH 6.29 and aw 0.986 meanwhile sous vide chicken rice products, with pH 6.35 and aw 0.984, had microbiological and chemical stability from day 0 until week 4.Generally, better aroma and flavour retention were obtained in the sous vide products compared to the traditional cooked products.Texture changed significantly (P<0.05) when different cooking method or timetemperature combination was used but not for storage duration.Chicken keels were also stable from any microbiological spoilage. TBA test showed significant (P<0.05)changes in rancidity although the sensory mean scores were only at the low range of 1-3. Although the preference of panelists towards the sous vide products was not significant(P < 0.05),sous vide products showed their benefits as better retention in aroma and flavour, lower cook loss,juicier and more tender compared to the traditionally cooked products